Regulation of synaptic connectivity in schizophrenia spectrum by mutual neuron-microglia interaction - Ricarda Breitmeyer; Sabrina Vogel; Johanna Heider; Sophia-Marie Hartmann; Richard Wüst; Anna-Lena Keller; Anna Binner; Julia C. Fitzgerald; Andreas J. Fallgatter; Hansjürgen Volkmer (Communications Biology, 2023)
Abstract The examination of post-mortem brain tissue suggests synaptic loss as a central pathological hallmark of schizophrenia spectrum (SCZ), which is potentially related to activated microglia and increased inflammation. Induced pluripotent stem cells serve as a source for neurons and microglia-like cells to address neuron-microglia interactions. Here, we present a co-culture model of neurons and microglia, both of human origin, to show increased susceptibility of neurons to microglia-like cells derived from SCZ patients. Analysis of IBA-1 expression, NFκB signaling, transcription of inflammasome-related genes, and caspase-1 activation shows that enhanced, intrinsic inflammasome activation in patient-derived microglia exacerbates neuronal deficits such as synaptic loss in SCZ. Anti-inflammatory pretreatment of microglia with minocycline specifically rescued aberrant synapse loss in SCZ and reduced microglial activation. These findings open up possibilities for further research in larger cohorts, focused clinical work and longitudinal studies that could facilitate earlier therapeutic intervention.